By the remainder theorem of polynomial division, the complete equation is f(-3) = 11
<h3>How to complete the blanks?</h3>
The equation is given as:
f(x)/x + 3
Set the divisor to 0
x + 3 = 0
Solve for x
x = -3
Given that the quotient has a remainder of 11.
It means that:
f(-3) = 11
Hence, the complete equation is f(-3) = 11
Read more about remainder theorem at:
brainly.com/question/13328536
#SPJ1
Answer:
-8 - 1/3n ≤ - 25
solving-n E [51,+oo] , {n|n ≤ 51}
answer-n ≤ 51
Step-by-step explanation:
I hope its help
Brainliest me pls
#CARRYONLEARNING
Answer:
To get the function <em>g</em>, shift <em>f </em>down by 8 units.
Step-by-step explanation:
The constant - 8 at the end of function g(x) suggests the parent function f(x) was translated 8 units down.
Answer:
-3
3
9
33
Step-by-step explanation:
y=6x+3
In the chart theres a column for x. The numbers in that column gets subsituted for x in y=6x+3. For example, the first number in the chart is -3. The equation would then be y=6(-3)+3. You then solve from there.
Hope this helps <3
Answer:
m=3
Step-by-step explanation:
-4m+7= -5
Combine like terms.Put +7 on other side.
-4m= -5-7
-4m= -12
It's -4 times m = -12 right ?
So the answer is m=3 because m= -12/-4